Analisis Deskriptif Soal-Soal Pada Buku Ajar Matematika Sekolah Dasar Kelas IV Kurikulum 2013 Ditinjau Dari Aspek Kognitif TIMSS - Usmawati Kasanah, Nurul, Prof. Dr. Budi Murtiyasa, M.Kom (2017)
This study aimed to analyze the problems in the textbook thematic fourth grade were observed from the cognitive aspects in TIMSS 2011. The cognitive aspect according to the TIMSS 2011 include knowledge (knowing), applying (applying), and reasoning (reasoning). For the selected books thematic class IV consists of one theme to theme 9 and published by the Ministry of Education and Culture of the Republic of Indonesia Year 2014. The research was conducted by analyzing the questions contained in the textbook thematic review of aspects of cognitive TIMSS 2011. The results shows that: (1) the cognitive aspects of knowledge (knowing) the book that examined contained 256 questions with the percentage of 54%, (2) the cognitive aspects of applying (applying) to books studied contained 123 questions with a percentage of 26%, (3) cognitive aspects reasoning (reasoning) to books studied contained 95 questions with a percentage of 20%. From these results it can be concluded that the book too much emphasis on the aspect of knowledge (knowing) and not in accordance with the standards of TIMSS 2011. Thus, the book still needs to be revised to obtain perfection as a reference for the learning process. Keywods: items, textbooks, cognitive level